Efektifitas Pembelajaran Daring di Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Bengkulu - Hilyati Milla; Yosha Nanda Eka Putri (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aims to determine the effectiveness of online learning at the Faculty of Teacher Training and Education, University of Muhammadiyah Bengkulu. This type of research is qualitative research. Sources of data in this study the authors use 2 sources of primary data and secondary data. The subjects in this study were lecturers at the Faculty of Teacher Training and Education, University of Muhammadiyah Bengkulu with the position of Head Lector. Data collection techniques using observation, interviews and documentation. The data analysis technique uses data reduction, data display and Conclusion Drawing/verification. The results of this study showed that most of the lecturers at the Faculty of Teacher Training and Education at the University of Muhammadiyah Bengkulu found online learning to be less effective.